Development, Validity, and Reliability of Adolescent Motivation Inventory-Cerebral Palsy - Moslem Dehghanizadeh; Malahat Akbarfahimi; Armin Zareiyan; Farzaneh Yazdani; Mitra Khalafbeigi (Iranian Rehabilitation Journal)
Objectives: Motivation is the most influential factor in the drive and performance of adolescents with cerebral palsy (CP). As identification and analysis of volition in Iranian adolescents with CP seem to be essential, designing appropriate tools for assessing their motivation is crucial. To achieve this goal, we developed an adolescent motivation inventory-CP (AMI-CP) and evaluated its psychometric properties. Methods: In the first phase, item generation was conducted. Next, in the second phase, face and content validities of the items were assessed. Moreover, construct validity was assessed by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). A total of 304 adolescents with CP participated in the EFA, while 210 adolescents with CP participated in the CFA. Afterward, convergent and discriminant validities of the inventory were measured. Moreover, reliability was evaluated by calculating Cronbach α, McDonald’s omega, average inter-item correlation, composite, and test re-test reliability. Lastly, the standard error of measurement (SEM) and the minimum detectable change (MDC) were applied. Results: Five factors with 22 items were extracted by EFA, accounting for 50.42% of the variance. The results of model fit indexes confirmed the goodness-of-fit of the final model with 20 items. In addition, the AMI-CP had a Cronbach α value of 0.75 and an intra-class correlation coefficient of 0.94. Moreover, the SEM and MDC of the inventory were 2.63 and 7.31, respectively. Discussion: The AMI-CP is a helpful measure of motivation in adolescents with CP. This inventory can enhance the assessment of the CP adolescents’ motivation by evaluating values, interests, personal causation, and physical and social environments.